Comparison of Manning's Roughness Coefficient Estimation Methods Based on Channel Geometry and Bed-Load Sediment Characteristics in the Way Tapus River - Ayudia Hardiyani Kiranaratri; Miskar Maini (Universitas Islam Raden Rahmat, Malang, 2025)
Natural and artificial rivers contain bed-load sediment materials with varying shapes and grain sizes influencing flow resistance, velocity, and discharge. This resistance is expressed by the Manning roughness coefficient (n), whose accurate estimation is essential for hydraulic analysis. While n is commonly obtained from Manning’s table, alternative methods based on hydraulic parameters, channel geometry, and sediment characteristics, such as the Keulegan, Mayer-Peter-Muller, Lane and Carlson, Henderson, Raudkivi, Subramanya, and Wong and Parker methods, can be applied for more site-specific estimations. This study utilized primary field data and secondary data to estimate n values using various approaches. The n values ranged from 0.096–0.148 (hydraulic parameters), 0.069–0.136 (channel geometry), and 0.009–0.018 (sediment-based methods). Error analysis comparing calculated and observed discharges showed that the channel geometry method yielded the most accurate results with an average error of 15.59%. In contrast, other methods resulted in significantly higher errors. Thus, the channel geometry approach is recommended for estimating the Manning coefficient in the Way Tapus River.